1988
DOI: 10.1227/00006123-198811000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Lumbar Injection of Ringer's Lactate Solution in Chronic Subdural Hematomas: A Series of 100 Cases

Abstract: A series of 100 patients underwent surgical treatment for chronic subdural hematomas between 1979 and 1987. The procedure consisted of craniectomy with a 30-mm trephine, irrigation and drainage of the hematoma, laceration of the outer and inner membranes, and lumbar intrathecal injection of Ringer's lactate solution for immediate cerebral reexpansion (average injection, 130 ml). This technique gave the following results: 2% mortality, 2% moderate morbidity, and 96% recovery. The recovery of the patients was ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…Other surgeons propose additional peri-operative lumbar intrathecal injection of Ringer's lactate solution after CSDH evacuation [5] or replacement of haematoma with oxygen after subdural tapping [1,2]. Prospective clinical trials with continuous irrigation-drainage have also been performed [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other surgeons propose additional peri-operative lumbar intrathecal injection of Ringer's lactate solution after CSDH evacuation [5] or replacement of haematoma with oxygen after subdural tapping [1,2]. Prospective clinical trials with continuous irrigation-drainage have also been performed [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been reported for reducing the amount of air remaining in the hematoma cavity and thus avoiding rebleeding. These include lumbar intrathecal injection of physiological saline or Ringer's solution during surgery [12,[37][38][39], the replacement of the hematoma with carbon dioxide gas [40] or oxygen [41], craniotomy without closure of the dura or replacing the bone plate [20], an implantation of a subcutaneous reservoir with a catheter introduced into the subdural cavity [41], or an overhydratation in the Trendelenburg position [2]. In 1988 Probst [43] reported a series of patients with CSDH treated by placement of a subdural-peritoneal shunt.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative collapse of the brain and intracranial hypotension have often gone hand in hand, for in itself intracranial hypotension is associated with lowered states of consciousness, reversible when the pressure rises [12]. The incidence of postoperative intracranial hypotension was 3% but in no case was there need for intrathecal or intraventricular injection of fluid, which has been advocated as a good method for producing the reexpansion of the brain [38]. McKissock et al [32] reported decreased intracranial pressure in 3.3% of 212 patients with hematomas, but recently higher percentages (10%) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and radiological risk factors for developing seizures associated with chronic SDH include brain atrophy, mixed-density SDH, prior stroke, and low Glasgow Coma Scale (GCS) at presentation [16][17][18]. In patients with chronic SDH who underwent surgical intervention, the incidence of seizures is between 5 and 22 % in the acute postoperative period [17][18][19][20][21]. Predictors of seizures in this group include low GCS on admission, low postoperative GCS, acute-on-chronic SDH, and open craniotomy [17,18].…”
Section: Epidemiology Of Seizures In Subdural Hematomamentioning
confidence: 99%